Bibliometric and co-occurrence study of the production of cellulase from Bacillus (2000–2025) - Maryyam, T.; Rahayu, S.; Sukmawati, D.; Anvar, A.H.; Shakir, H.A.; Khan, M.; Ul-Haq, J.; Irfan, M. (International Journal of Biology and Chemistry, 2025)
Cellulase refers to a group of enzymes that can break down cellulose, the most widespread organic polymer on Earth. It is one of the most important industrial enzymes due to its application in the production of valuable products such as biofuels, papers and textiles. Many microorganisms naturally produce cellulase, including Bacillus species. This study presents detailed bibliometric analysis of Bacillus cellulase. The core objective of this study is to provide global research trends related to Bacillus cellulase. It highlights leading authors, institutions, countries and sources that have major contributions in this area of research. The Scopus Dataset of 2212 documents was included for analysis. VOSviewer and Biblioshiny software were employed for bibliometric analysis and visualization. The most prolific author was Zhang Y with highest number of publications (45) and citations. China ranked first among top contributing countries, followed by India with second position. This study will help researchers in understanding global research trends on Bacillus cellulase. Keywords: Bacillus, cellulase, Bibliometric study, VOSviewer, Biblioshiny.